Serum level of procollagen-I-peptide in patients on maintenance hemodialysis - Uji, Yoshinori; Motomiya, Yoshihiro; Okabe, Hiroaki; Okajima, Eigoro (Journal of Japanese Society for Dialysis Therapy, 1992)
The serum level of C-terminal procollagen-I-peptide was measured in 49 patients with chronic renal failure on maintenance hemodialysis, and we consider here the clinical importance of this peptide in the diagnosis of renal osteodystrophy associated with chronic renal failure. The serum level of procollagen-I-peptide was 644.9±244.5ng/ml in male patients (n=27), and 697.7±279.7ng/ml in female patients (n=22), both levels being significantly higher than the 390.7±130.4ng/ml (n=24) in our sample of healthy subjects. A comparative study between two patient subgroups, one with a short history of hemodialysis (less than 36 months) and the other with a long history of hemodialysis (longer than 60 months) showed an apparently higher level of procollagen-I-peptide in the latter group. Based upon these results, we conclude that in patients with chronic renal failure on maintenance hemodialysis, the serum level of procollagen-I-peptide may be clinically useful in the diagnosis of ranal osteodystrophy, just as conventional protein-containing markers such as alkaline phosphatase and bone γ-carboxyglutamic acid are.